Analysis of The Use of Satirical Language by Netizens Towards Jokowi on The @Folkative Account - Siti Nur Amelia; Ahada Wahyusari; Zaitun (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study discusses the Use of Sarcasm Style of Language Towards Jokowi in the Comments Column of the @Folkative Account in March and April 2022. The purpose of this study is to describe the form of sarcasm style of language found in the comments column of the re-upload of Mr. Jokowi's statement on the @folkative account in March and April 2022. This study is qualitative with a descriptive method. The instrument used is the researcher himself and is supported by an analysis guideline table that helps researchers to summarize the data obtained. The data in this study are in the form of dialogue quotes or sentences from the film Perempuan Tanah Jahanam by Joko Anwar. The data collection technique used to obtain research data uses the listening and note-taking technique. The analysis technique of this study uses a narrative analysis method and is more conceptual to find, identify, process and analyze documents to find out the form and understand the meaning, and its relevance. Based on the results of the study, it was found that the form of sarcasm style of language found in the comments column of the re-upload of Mr. Jokowi's statement on the @folkative account in March and April 2022 was 10, namely: ) rejection; (2) conveying prohibitions; (3) conveying orders; (4) conveying information; (5) conveying affirmations; (6) conveying questions; (7) conveying comparisons; (8) conveying similarities; (9) conveying opinions; (10) greetings. The most dominant forms of rejection and conveying opinions were found, netizens or users commented on the Folkative Instagram account in March and April 2022 to Jokowi. They commented with harsh words that were inappropriate for the Head of State.